Phosphorus Plays Key Roles in Regulating Plants’ Physiological Responses to Abiotic Stresses - Khan, Fahad; Siddique, Abu Bakar; Shabala, Sergey; Zhou, Meixue; Zhao, Chenchen (Plants (Basel), 2023)
Phosphorus (P), an essential macronutrient, plays a pivotal role in the growth and development of plants. However, the limited availability of phosphorus in soil presents significant challenges for crop productivity, especially when plants are subjected to abiotic stresses such as drought, salinity and extreme temperatures. Unraveling the intricate mechanisms through which phosphorus participates in the physiological responses of plants to abiotic stresses is essential to ensure the sustainability of agricultural production systems. This review aims to analyze the influence of phosphorus supply on various aspects of plant growth and plant development under hostile environmental conditions, with a special emphasis on stomatal development and operation. Furthermore, we discuss recently discovered genes associated with P-dependent stress regulation and evaluate the feasibility of implementing P-based agricultural practices to mitigate the adverse effects of abiotic stress. Our objective is to provide molecular and physiological insights into the role of P in regulating plants’ tolerance to abiotic stresses, underscoring the significance of efficient P use strategies for agricultural sustainability. The potential benefits and limitations of P-based strategies and future research directions are also discussed.